2015
DOI: 10.1080/17429145.2015.1070208
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between seedlings of the invasive treeAilanthus altissimaand the native treeRobinia pseudoacaciaunder low nutrient conditions

Abstract: The allelopathic effect of A. altissima and the nitrogen fixing ability of R. pseudoacacia make the interaction between these two species important to community dynamics. A replacement series greenhouse experiment was used to investigate the type of interaction between seedlings of A. altissima and R. pseudoacacia at high and low soil nutrition states. Also, seeds of A. altissima from its native (China) and invasive ranges (USA) were used to compare the effect of the different seed sources on the interaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
3
0
1
Order By: Relevance
“…At any particular time, the overall result of competition or facilitation is a cumulative effect. Therefore, the results from this study complement previous research [46], which showed that seedlings of R. pseudoacacia have a facilitative effect (due to the effect of nitrogen fixation on soil nitrogen availability) on the growth of A. altissima seedlings when the soil nutrient level may be low. In locations with equal numbers of both species, R. pseudoacacia will also facilitate the growth of A. altissima.…”
Section: Does the Interaction Between Species Change From Seedling Tosupporting
confidence: 78%
See 2 more Smart Citations
“…At any particular time, the overall result of competition or facilitation is a cumulative effect. Therefore, the results from this study complement previous research [46], which showed that seedlings of R. pseudoacacia have a facilitative effect (due to the effect of nitrogen fixation on soil nitrogen availability) on the growth of A. altissima seedlings when the soil nutrient level may be low. In locations with equal numbers of both species, R. pseudoacacia will also facilitate the growth of A. altissima.…”
Section: Does the Interaction Between Species Change From Seedling Tosupporting
confidence: 78%
“…Consequently, A. altissima's ability to negatively affect R. pseudoacacia's growth rate in our study may be due to A. altissima's ability to better compete for below-ground resources, which was also found in greenhouse studies of seedlings [47]. Thus, the cause of inhibition by A. altissima on the much larger, above-ground R. pseudoacacia ought to be the result of either more effective below-ground competition or a negative effect of allelopathy on root growth and the nitrogen-fixing bacteria associated with R. pseudoacacia [46,48].…”
Section: What Are the Forest Management Implications Of This Research?mentioning
confidence: 59%
See 1 more Smart Citation
“…In order to break the dormancy of A. altissima seeds, different methods have been tested. Gibberellic acid [34,35], cold stratification [3,33,[36][37][38][39][40][41], wet or dry stratifications [42,43], and sulfuric acid or boiling water [33] have been applied to the seeds over different periods of time. From the results reported, cold stratification seems to give the highest germination rates.…”
Section: Seed Dormancymentioning
confidence: 99%
“…Fakat türün hızlı büyüme özelliğinden dolayı birçok bölgede peyzaj çalışmalarında kullanılmaktadır [38]. Yine tür hakkında yapılan çalışmalar incelendiğinde düşük besin konsantrasyonlu topraklarda iyi gelişebilmesinin yanında [39] yüksek N içeriğine sahip ve su kıtlığının olduğu alanların türün gelişimini olumsuz etkilemediği bulunmuştur [40]. Li ve arkadaşları özellikle yüksek N içerikli toprakların türün gelişimini hızlandırdığını belirlemişlerdir [40].…”
Section: öZunclassified